The effects of olive oil consumption on cognitive performance: a systematic review - Fazlollahi, Asra; Motlagh Asghari, Kimia; Aslan, Cynthia; Noori, Maryam; Nejadghaderi, Seyed Aria; Araj-Khodaei, Mostafa; Sullman, Mark J. M.; Karamzad, Nahid; Kolahi, Ali-Asghar; Safiri, Saeid (Frontiers in Nutrition, 2023)
Introduction: The Mediterranean diet is marked by the regular intake of olive oil, which may play a role in preventing and protecting against cognitive deterioration and dementia. The strength of these effects have been examined by several recent randomized controlled trials (RCTs), but their findings have not been consistent. In light of this inconsistency, the present study performed a systematic review to examine the relationship between the consumption of olive oil and cognition. Methods: The Web of Science, Scopus, PubMed, and Google Scholar were systematically searched up to August 11, 2023. The review included RCTs, cross-sectional studies, cohort studies and case-control studies that explored the impact of olive oil consumption on cognitive performance among those older than 55 years old. Studies were excluded if they employed a design other than those mentioned above, involved participants under 55 years old, or did not specifically examine the cognitive effects of olive oil consumption. The quality of the included studies were measured using the Cochrane risk-of-bias tool and the Newcastle Ottawa Scale checklists. Results: Eleven studies were identified, which were comprised of four cross-sectional studies, four prospective cohort studies and three RCTs. The cohort studies and RCTs consistently found that olive oil consumption had a favorable effect on cognitive performance across a number of cognitive domains over time. Similarly, all of the cross-sectional studies reported that the consumption of olive oil was positively associated with cognitive health. Conclusions: The consumption of olive oil was found to enhance cognitive functioning and to reduce cognitive decline. Further large-scale investigations are required to strengthen this conclusion.